Assessing the Effects of the COVID-19 Pandemic on the Aviation Sector and Exploring Strategies for Industry Recovery - Roba Hasaneya; Khadija Mohammed; Swathi Shankar; Ignatius Fernando; Chaitanya Sonambekar; Nikita Garg (AIBPM Publisher, 2023)
One of the most impacted industries among all, is the Airlines industry. Airlines need to study the consequences of a pandemic, what is important is that they adapt to the uncertainty and complex changes. Companies must understand how to manage their capabilities, strategy, mission, and vision, with a fast and changing environment. Each airline can get the benefit of having a low-cost strategy and use the cargo shipment strategy that makes it easy to ship different products. Basically, reaching efficiency and effectiveness to lead the uncertain changes. For the research report it considers the highly affected industry in covid era. Qatar airways operated in a high premium business model but in covid times, demand of the luxury segment got affected. Indigo does their business mainly in India, so they are the worst hit in these times since India shows the second highest number of covid cases in the world. Due to the resurgence of Covid-19, Cathay Pacific have struggled with staff rostering due to Hong Kong’s strict quarantine rules.